The roles and relevancy of rooftop garden to the society in urban area - Nor Azhar, Ali Saifuddin; Ibrahim, Putri Haryati (2016)
setting so that the introduction of this vertical landscape can be beneficial to the residents living in high-rise building and help to contribute towards sustainable urban development in Malaysia. This study is to investigate the usage level of the rooftop garden and public behavior towards the rooftop garden in urban areas. To obtain good information this study focuses on the public opinion and perceptions about the practicing of rooftop garden in urban areas. The method and scope of research in this study are divided into several stages using both qualitative and quantitative methods. The research comprise literature review; achieve analysis, case studies, observation, survey, data analysis, result and recommendation. The questionnaire survey was distributed to 100 respondents where 50 respondents is from rooftop garden of Zeta Park, Setapak and another 50 respondents is from rooftop garden of Urban 360, Batu Caves. This study found that the rooftop garden is relevant and can be substitutes for a shortage of landed open space due to the roles of rooftop garden such as reduce the urban heat island, provide usable space, promote biodiversity and beautify the environment. This study has recommended several measures to address the issues for improvement of rooftop garden in Zeta Park, Setapak and Urban 360, Batu Caves.